Making Telescopes and Partying with the Stars: Amateur Astronomy in Spain during Franco's Dictatorship. (May 2016) - Ruiz-Castell, Pedro
Franco's dictatorship was characterized by an official narrative that criminalized the liberal tradition of previous periods. Such a discourse defined an ideologically correct science that censured the subordination of Spanish science to foreign influence and sought to create a new scientific tradition. However, recent studies have revised these aims and suggest that there was a continuity of scientific and technological programmes and practices before and after the Spanish Civil War. This paper contributes to these investigations with further evidence, focusing on several practices that characterized the development of amateur astronomy during this period. Special attention is paid to the development of amateur telescope making, the popularization of astronomy, and attempts to define astronomy as a discipline for sociability that developed in alternative spaces for instruction and socialization – and so avoided direct control from the dictatorial regime.